Disruptive Research and Innovation - Kai Li (Proceedings - IEEE International Parallel and Distributed Processing Symposium, 2016)
Ever since Clayton Christensen coined the terms "disruptive technologies" and "disruptive innovations" in 1990s, researchers and entrepreneurs love the word "disruptive" because disrupting current knowledge or products help us accelerate knowledge discoveries and moving the society into a new era. What is disruptive research? What is disruptive innovation? How do they happen? To answer such questions, in this talk, I will share my experience from co-leading the ImageNet project which built a knowledge base for computer vision and machine learning community, and from co-founding Data Domain, Inc. Which built deduplication storage ecosystems to replace tape library infrastructure in data centers.